Pengaruh Teknik Diskusi Dalam Bimbingan Kelompok Untuk Meningkatkan Keterampilan Berkomunikasi Siswa - Suci Archindany Anfa’u; Moesarofah Moesarofah (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2020)
Communication skills are one of the basic 21st century skills that require students to fulfill those skills, when students have communication skills they can actively follow learning activities in class. However, not all students can be skilled in communicating, because communication skills cannot be obtained automatically. Less skilled students communicate with the difficulties of actively participating in the learning activities and the Tribulation in the opinion, thereby inhibiting students ' self-development in learning. The purpose of this research is to examine the use of technical discussion techniques in group guidance on the communication skills of junior high school students. This research uses a quantitative approach with the research method of one group pre-Test post-Test design. The data collection methods used are the scale of communicating skills, observable, and interviews. The study used group guidance services with group discussion techniques given to 8 students of grade VIII in SMPN 3 Sidoarjo with low interval categories. The Group guidance service was conducted six times the meeting with a time allocation of 35 minutes. The data analysis techniques used in the study were non-parametric statistics using the Wilcoxon test with a significance limit of 0.05. Results of analysis obtained by 0.012 ? 0.05, then concluded there is a significant influence in the use of Group guidance Services with group discussion techniques to communication skills in grade VIII students at SMPN 3 Sidoarjo.